pengembangan Development of an Ethnhomathematics Module Based on Local Culture in Improving Elementary School Students' Mathematical Literacy Abilities: Pengembangan Modul Etnhomatematika Berbasis Budaya Lokal Dalam Meningkatkan Kemampuan Literasi Matematika Siswa Sekolah Dasar - sabahul khair; Elianawati Elianawati; Rusilowati Rusilowati (Perkumpulan Doktor Indonesia Maju (PDIM), 2023)
The aim of this research is to discuss the feasibility of teaching materials that use ethnomathematics modules based on local culture in mathematics learning in elementary schools. The research method uses literature studies from national and international journals on mathematics teaching materials. The data analysis technique uses content analysis. The research results show that the use of teaching materials in the form of ethnomathematics modules as teaching materials has been widely used in mathematics learning. On average, the feasibility of the teaching materials developed is in the valid and very valid categories and the response of teachers and students to the use of teaching materials is positive and very positive. With this literature study, researchers can combine the use of ethnomathematics modules as a learning medium.